The American people : creating a nation and a society - Nash, Gary B.; Jeffrey, Julie Roy (New York : Harper & Row, 1986)
Contents: v.1. To 1877 - v.2. Since 1865
The Library has volume one only. Includes bibliographies and index
Keywords: United States -- History